Antidiabetic Effect of Rehmanniae Radix Based on Regulation of TRPV1 and SCD1 - Liu, Ye; Zhu, Ruizheng; Liu, Bei; Wang, Wuqing; Yang, Ping; Cao, Zhonglian; Yang, Xiaolei; Du, Wandi; Yang, Qing; Liang, Jingru; Hu, Jiarong; Ma, Guo (Frontiers in Pharmacology, 2022)
Purpose: This study aimed to disclose the antidiabetic mechanisms of Rehmanniae Radix (RR). Methods: Antidiabetic effect of RR was studied by the STZ-induced diabetes mellitus (DM) rats and the HepG2 cells with insulin resistance (IR). Antidiabetic targets and signaling pathways of RR were confirmed by the network pharmacology and transcriptome analysis as well as the HK2 cell induced by high glucose (HG). Results: After the DM rats were administrated RR extract (RRE) for four weeks, compared to that in the model group, body weight of the DM rats was 10.70±2.00% higher, the fasting blood glucose (FBG), AUC of oral glucose tolerance test and insulin sensitivity test of the DM rats were 73.23±3.33%, 12.31±2.29%, 13.61±5.60% lower in the RRE group, respectively. Compared to that of the model group, the glucose uptake of HepG2 cell with IR increases 45.76±3.03% in the RRE group. The RR-components-targets-DM network with 18 components and 58 targets was established. 331 differentially expressed genes (DEGs) were identified. TRPV1 and SCD1 were important DEGs by the intersectional analysis of network pharmacology and renal transcriptome. TRPV1 overexpression significantly inhibited apoptosis and oxidative stress of HK2 cell induced by HG, while SCD1 overexpression induced apoptosis and oxidative stress of HK2 cell induced by low and high glucose. Compared to that in the HG group, mRNA and protein expression of TRPV1 increased 3.94±0.08 folds and 2.83±0.40 folds in the presence of RRE (100 μg/mL), respectively. Conclusion: In summary, RR displayed inspiring antidiabetic effect by reducing FBG and IR, up-regulating the mRNA and protein expression of TRPV1 as well as down-regulating mRNA expression of SCD1. Induction of TRPV1 and inhibition of SCD1 by RR was possibly one of its antidiabetic mechanisms.